Pemodelan kepuasan konsumen dan niat berkunjung kembali terhadap Restoran Cocorico - Christopher Sanjaya; Fransisca Mulyono (Universitas Kristen Maranatha, 2023)
The study objective is to determine the factors that most influence customer satisfaction and revisit intention in Cocorico Restaurant, testing the mediation relationship between customer satisfaction and variables that influence revisit intention, and investigate variables that influence customer revisit intention in casual dining restaurants in the city of Bandung. The type of research is explanatory research. Data was collected by distributing questionnaires to customers at the Cocorico Restaurant. The proposed model was modeled using PLS-SEM with a sample size of 176 respondents. Food quality, quality of service, atmosphere, and perceived value were found to have a significant positive influence on customer satisfaction. Food quality, quality of service, atmosphere, and customer satisfaction were found to have a significant positive influence on revisit intention. Perceived value was found not to have a significant value on revisit intention. Customer satisfaction partially mediates food quality, quality of service and atmosphere on revisit intention. Customer satisfaction fully mediates perceived value on revisit intention. Cocorico Restaurant needs to focus on improving the quality of food and perceived value of the restaurant as well as maintaining the quality of service and atmosphere to increase customers revisit intention.